The Dispute over the Geographical Application of the Svalbard Treaty: Into a New Phase, An Essay in Honor of Ted L. McDorman - Henriksen, Tore (Ocean Development & International Law, 2024)
Under the 1920 Treaty concerning the archipelago of Spitsbergen (Svalbard Treaty), the contracting parties recognize the full and absolute sovereignty of Norway over the archipelago. The sovereignty is to be exercised subject to the stipulations of the Treaty, which include equal rights of the contracting parties to fish and hunt on the territory of Spitsbergen and its territorial waters. Consistent with the developments of the law of the sea, Norway has claimed sovereign rights over the continental shelf and established 200 nautical miles (NM) zones off its coast, including Svalbard. Norway established a 200NM Fisheries Protection Zone off the coast of Svalbard. Several contracting parties claim that the equal rights under the Svalbard Treaty are applicable in the maritime zones claimed or established after 1920. This is disputed by Norway by referring to the wording of the Treaty, which stipulates that it is applicable within the 12-NM territorial waters. Owners and captains of vessels flagged in other contracting parties have protested and argued that the arrest and prosecution for illegal fishing in the 200-NM zone off Svalbard violated their equal rights of fishing. The Court had not addressed the question of the applicability of the Treaty provisions until 2023. In a civil case before the Supreme Court, a Latvian shipowning company argued that the snow crab regulations on the continental shelf in the Barents Sea were void as they violated the equal rights of contracting parties under the Svalbard Treaty to fish on the continental shelf. The Supreme Court concluded that the treaty provisions were not applicable beyond the 12-NM territorial sea of the archipelago. An attempt by the same company at international litigation through investment arbitration was also unsuccessful. As the dispute issue is settled within the Norwegian legal system, the dispute enters into a new phase.